METHOD FOR JOINT OPTIMIZATION FEEDFORWARD ARTIFICIAL NEURAL NETWORKS WEIGHTS AND STRUCTURE IN DEEP MULTI-AGENT REINFORCEMENT LEARNING - V. I. Petrenko (Современная наука и инновации, 2022)
Increasing the intelligence of tasks solved using mobile cyber-physical systems (MCPS) requires the use of artificial neural networks (ANNs) and methods of multi-agent deep reinforcement learning (MDRL).